The Effectiveness Of Health Education For Promoting Knowledge Level Of Pregnant Women About Pregnancy Danger Signs - maya, aminah (Journal of health research and technology, 2026)
Background:Pregnancy disorders or complications must be detected earlier to prevent more dangerous risks for pregnant women and their fetuses. Mother's knowledge about pregnancy danger signs needs to be improved so that early detection of complications can be carried out earlier and treatment of complications is not too late. Promoting knowledge of pregnant women can be carried out through health education activities using a booklet. Objective: To analyze the effectiveness of booklet for promoting knowledge level of pregnant women about pregnancy danger signs. Methods:This research was Quasi Experiment with one group pre and post test design. The Population was all pregnant women that checked her pregnancy in 2022 and the sample collection technique using Purposive Sampling with 50 respondents and divided into 2 groups, intervention group and control group. This study was held in Maternity Clinic of Husniyati, Palembang, Indonesia. Results: there were differences in values before and after intervention using the Wilcoxon Test. P value: 0.008 (<0.05),statistically it means that health education using booklet media has effectively proven on promoting the knowledge level of pregnant women about the pregnancy danger signs. Conclusion: The use of booklet can effectively promote the knowledge level of pregnant women about the pregnancy danger signs Keywords : Booklet, Knowledge level, Pregnant Women, Pregnancy Danger Signs